Analysis of the Impact of Maintaining and Changing Credit Ratings on the Credit Spread on the Polish Corporate Bond Market in the Period 2010–2017 - Orzechowski, Arkadiusz (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2019)
The purpose of the article is to determine the impact of maintaining and changing credit ratings formulated by the Moody’s rating agency on the credit spread on the Polish debt market in the period 2010–2017. It seeks to draw conclusions on the efficiency of the Polish debt market with respect factors including raising, maintaining at the current level or lowering the rating. The methodology used in the paper is based on the standard procedure for studying events. The results of the conducted research are not unequivocal. While they indicate a correct response of the credit spread to changes in the credit ratings, the results obtained are not confirmed by statistical significance tests.